KnightShift: Scaling the Energy Proportionality Wall through Server-Level Heterogeneity - Wong, Daniel; Annavaram, Murali (2012 45th Annual IEEE/ACM International Symposium on Microarchitecture, 2012)
Server energy proportionality has been improving over the past several years. Many components in a system, such as CPU, memory and disk, have been achieving good energy proportionality behavior. Using a wide range of server power data from the published SPEC power data we show that the overall system energy proportionality has reached 80%. We present two novel metrics, linear deviation and proportionality gap, that provide insights into accurately quantifying energy proportionality. Using these metrics we show that energy proportionality improvements are not uniform across various server utilization levels. In particular, the energy proportionality of even a highly proportional server suffers significantly at non-zero but low utilizations. We propose to tackle the lack of energy proportionality at low utilization using server-level heterogeneity. We present Knight Shift, a server-level heterogenous server architecture that introduces an active low power mode, through the addition of a tightly-coupled compute node called the Knight, enabling two energy-efficient operating regions. We evaluated Knight Shift against a variety of real-world data center workloads using a combination of prototyping and simulation, showing up to 75% energy savings with tail latency bounded by the latency of the Knight and up to 14% improvement to Performance per TCO dollar spent.